Global Income and Wealth Inequality in Malaysia (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
The article examines Malaysia's economic transformation since independence, focusing on shifts in income and wealth distribution. It discusses the country's move from agrarian to diversified open economy, emphasizing the complexities in achieving equitable prosperity. The analysis employs measures like the Gini coefficient and explores historical, socio-cultural, and policy-driven factors influencing economic disparities. Comparisons with the Philippines provide insights, and the article calls for ethical considerations in economic policies. The conclusion emphasizes the need for targeted interventions, financial literacy, private sector engagement, and an inclusive approach to foster sustainable economic growth with equal distribution of benefits